THE EFFECT OF COLLABORATION ON OMANI STUDENTS’ WRITING: A COMPARISON BETWEEN INDIVIDUAL, PAIR AND GROUP WORK - Al Tai, Yasmeen (European Scientific Journal, ESJ, 2015)
Recently, there has been a lot of discussion about the integration of collaborative writing in L2 classrooms. Collaboration is likely to have a positive effect on writing. However, none of the studies on collaborative writing have been conducted in an Arabic context where learners seem to be in favour of working individually. The current study investigates the effect of collaboration on L2 Omani students writing and expands the discussion to the attitudes of those learners to such collaboration. The data is collected from 41 students selected from two regional schools in Oman. Learners were firstly asked to complete a questionnaire about their attitudes towards collaborative writing. Then, they were divided into individuals, pairs and groups to work in a writing task followed by self reflections for pairs and groups. The analysis and interpretations of data found that collaborative writing positively affects accuracy, fluency and lexical resources of the texts. Moreover, learners generally perceive collaborative writing positively. It was concluded that collaborative writing tasks, groups rather than pairs, have an advantage over autonomous writing to some extent. The findings suggest that collaborative writing should be introduced gradually in writing classes and integrated in the actual writing process.